Archival Mocking As Feminist Praxis: A Rhetorical Repurposing of A Vindication of the Rights of Brutes. Issue 1 (2nd January 2021) - Muller, S. Marek
Abstract: My ironic rereading of Thomas Taylor's Vindication of the Rights of Brutes accomplishes five tasks: First, I provide readers with an introduction to Thomas Taylor (one of protofeminist Mary Wollstonecraft's harshest critics) and the satiric text he wrote specifically to undermine her. Second, I assess how the inherent instability of textual meaning provides a rationale for ironically reclaiming a text in the service of feminist emancipation (and, in the case of Taylor's Vindication, animal emancipation). Third, I offer the ecological metaphor of "repurposing" as justification for what I call "mocking as method." Fourth, using this ironic methodology, I ironize Taylor's already-ironic Vindication by reading it literally, thus rhetorically repurposing Taylor's textual garbage into a coherent vegan ecofeminist argument for animal rights. Finally, I theorize mocking as method as a rhetorical tool suitable not only for advancing vegan ecofeminist argumentation, but also for feminist criticism writ large. By attending to the instability of meaning in a text's ever-changing contexts, mocking as method moves critics from simply trashing a garbage text toward rhetorically repurposing it to advance arguments for social justice. If done well, this technique not only avoids wasting a text but can empower the marginalized and contribute to the composition of complex, sustainable rhetorical canons.